A Randomized Implementation Study of Trauma-Focused Cognitive Behavioral Therapy for Adjudicated Teens in Residential Treatment Facilities. (May 2016) - Cohen, Judith A.; Mannarino, Anthony P.; Jankowski, Kay; Rosenberg, Stanley; Kodya, Suzanne; Wolford, George L.
Adjudicated youth in residential treatment facilities (RTFs) have high rates of trauma exposure and post-traumatic stress disorder (PTSD). This study evaluated strategies for implementing trauma-focused cognitive behavioral therapy (TF-CBT) in RTF. Therapists ( N = 129) treating adjudicated youth were randomized by RTF program ( N = 18) to receive one of the two TF-CBT implementation strategies: (1) web-based TF-CBT training + consultation (W) or (2) W + 2 day live TF-CBT workshop + twice monthly phone consultation (W + L). Youth trauma screening and PTSD symptoms were assessed via online dashboard data entry using the University of California at Los Angeles PTSD Reaction Index. Youth depressive symptoms were assessed with the Mood and Feelings Questionnaire–Short Version. Outcomes were therapist screening; TF-CBT engagement, completion, and fidelity; and youth improvement in PTSD and depressive symptoms. The W + L condition resulted in significantly more therapists conducting trauma screening ( p = .0005), completing treatment ( p = .03), and completing TF-CBT with fidelity ( p = .001) than the W condition. Therapist licensure significantly impacted several outcomes. Adjudicated RTF youth receiving TF-CBT across conditions experienced statistically and clinically significant improvement in PTSD ( p = .001) and depressive ( p = .018) symptoms. W + L is generally superior to W for implementing TF-CBT in RTF. TF-CBT is effective for improving trauma-related symptoms in adjudicated RTF youth. Implementation barriers are discussed.